Faktor-Faktor yang Berhubungan dengan Keluarga Sadar Gizi - Holil M.Par'i; Ichwannudin Ichwannudin; Fred Agung Suprihartono; Aryani Sudja (Poltekkes Kemenkes Bandung, 2011)
Kadarzi is a family who knows the problems of nutrition and is able to prevent and overcome the problems ofmalnutrition in each family member. The family is called